2018
DOI: 10.1039/c7dt04232a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of novel platinum(ii) based AIE compound-encapsulated mesoporous silica nanoparticles for cancer theranostic application

Abstract: Advanced biomedical research has established that cancer is a multifactorial disorder which is highly heterogeneous in nature and responds differently to different treatment modalities, due to which constant monitoring of therapy response is becoming extremely important. To accomplish this, different theranostic formulations have been evaluated. However, most of them are found to suffer from several limitations extending from poor resolution, radiation damage, to high costs. In order to develop a better theran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…The analysis was facilitated through the observation of the 195 Pt satellites on 1 [Pt(CNC)(L)] complexes, 5,12−16,18,19,24,34,40−43 while for a few derivatives, short Pt•••Pt contacts of 3−4 Å have been reported. 15,38 Short Pt•••Pt contacts in such systems have also been intentionally constructed to induce aggregation-induced emission (AIE). 5,8,9,11,18,44,45 This has been observed in related cyclometalated Pt(II) complexes 3−6,37−39,43−46 and might also occur for the complexes presented here.…”
Section: ■ Introductionsupporting
confidence: 75%
“…The analysis was facilitated through the observation of the 195 Pt satellites on 1 [Pt(CNC)(L)] complexes, 5,12−16,18,19,24,34,40−43 while for a few derivatives, short Pt•••Pt contacts of 3−4 Å have been reported. 15,38 Short Pt•••Pt contacts in such systems have also been intentionally constructed to induce aggregation-induced emission (AIE). 5,8,9,11,18,44,45 This has been observed in related cyclometalated Pt(II) complexes 3−6,37−39,43−46 and might also occur for the complexes presented here.…”
Section: ■ Introductionsupporting
confidence: 75%
“…However, mesoporous silica-based materials have also been functionalized with metallodrugs of interest in cancer treatment, such as platinum compounds [7,8,9,10,11,12,13,14], titanium compounds [10,15,16,17,18,19,20,21,22,23], tin compounds [22,24,25] and even ruthenium photosensitizers [26], observing promising anticancer activity and a potential future application in clinical trials. The cellular action of these metallodrug-functionalized nanostructured silica-based materials showed that, in most cases, the nanosystems do not release the metallodrug to the biological medium (or the metallodrug release rates are very low), and they usually act as “non-classical” drug-delivery systems, whose cytotoxic activity is due to the action of the entire nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…The signal materials coupled to the functional vehicle are diverse, including but not limited to NIR dyes, radionuclide chelation agents (eg. DOTA) [ 184 ], two-photon dyes [ 181 ], MRI contrast agents, or aggregation induced emission (AIE) compounds [ 185 ]. They are usually conjugated to aptamers or the surface of silicas or are encapsulated into the shell of MSNs.…”
Section: Aptamer-functionalized Non-biological Materials For Therapeutic Applicationsmentioning
confidence: 99%
“…This concept might facilitate the instant detection or intervention in cancer therapy. Besides that, Pasha et al in 2018 designed an anti-EpCAM aptamer-functionalized MSNs system to encapsulate a dual functional compound, platinum-based “aggregation induced emission (AIE)” molecule (BMPP-Pt) [ 185 ] ( Figure 10 b). The component of BMPP-Pt is bis(diphenylphosphino)methane phenylpyridine platinum (II) chloride, holds potentials for theranostic applications in cancers by inducing cell apoptosis and emitting dose-dependent fluorescent signals.…”
Section: Aptamer-functionalized Non-biological Materials For Therapeutic Applicationsmentioning
confidence: 99%